Analisis Perbandingan Metode Pengujian Kekasaran Permukaan pada Material Polimer Dan Komposit - Review - Prasetyo, Dimas Eko (Jurnal Rekayasa Mesin, 2015)
The development of composite materials can be combined with the test material to obtain a composite material properties such as strength, hardness, wear, and surface roughness. The surface roughness of polymeric materials and composites can be tested in many ways, ranging from tactile method (profile measurement), focus variation (area measurement), fringe projection (area measurement), confocal laser scanning microscope (area measurement), and several other methods. Varied roughness testing on the surface will be compared to obtain the most suitable testing method to obtain the roughness of hybrid composite and composite ceramic specimens. The method used in this study is literature review. For hybrid composite material will be less suitable when using tactile method because of hybrid composite having a lower surface hardness. Additionally hybrid composite has a porosity value greater than the ceramic composite. This causes hybrid composite is more rugged than ceramic composite. Therefore with greater porosity will be suitable when using the roughness measurement with a microscope device such as fringe projection (area measurement), and confocal laser scanning microscope (area measurement).